Utilization of parabolic water wave transformation model for simulation tsunami wave pattern from quickbird data - Marghany, Maged (2012)
This paper utilized the parabolic wave transform model to simulate the characteristics of tsunami wave run from different QuickBird data over different locations along Aceh and kalutura, Sri-Lanka coastal waters. The wavelets transform model used to extract ocean wave parameters from QuickBird data. Also the relation between run-up height and erosion area was expressed with a run-up model. The predicted numerical results have been verified by comparing to available ground data have collected from NOAA web site measurements.